Cytotoxic Effects of Bulk-Fill Composites on L929 Fibroblast Cells - Aydın, Numan; Karaoğlanoğlu, Serpil; Oktay, Elif Aybala; Kılıç Süloğlu, Aysun (Brazilian Dental Science, 2021)
Objective: Unlike traditional composite resins, bulk-fill composite resins could be polymerized as thicker layers. This study aims to contribute to the field by investigating the cytotoxic effects of various bulk-fill composite resins on L929 mouse fibroblast cells in vitro. Material and Methods: In our study, six bulk fill and one conventional composite resin were used. Composite resin samples (8×4 mm) were prepared in a sterile cabinet by using a glass mod and polymerizing with a led light device (DTE LUX E, Germany). Composite samples (n:3) of which surface area was calculated according to ISO 10993-12: 2012 standards (3 cm2/ml), were kept in media for 24 h and 72 h in 37 oC incubator, their extracts were filtered in 1:1 and 1:2 proportion and were added on L929 mouse fibroblast cells. Cell viability was examined by the MTT assay and cell death by the LDH test. Cell viability results were evaluated using one-way analysis of variance (ANOVA) test (p